Sistem Absensi Berbasis Web dengan Swafoto Pada PT Gunung Selatan - Kelvin Kelvin; Kristia yuliawan (Jurnal Teknologi dan Informatika, 2025)
This study aims to design and implement a web-based employee attendance system with selfie at PT Gunung Selatan. The system was developed as a solution to common issues in manual attendance processes, such as fraud, location limitations, and low time efficiency. Using a Research and Development (RAD) approach and prototyping method, the system was built iteratively with integrated technologies including facial recognition, liveness detection, and GPS. Key features include real-time attendance logging, online leave requests, and integrated attendance reporting. The implementation results show significant improvements in operational efficiency, data accuracy, and transparency in employee attendance management. The system also has the potential for further integration with HR and payroll systems.